(E)-9-(4-Chlorostyryl)-3,4,5,6,7,9-hexahydro-2H-xanthene-1,8-dione - Lee, Jae Kyun; Pae, Ae Nim; Cho, Yong Seo; Cha, Joo Hwan (WILEY-BLACKWELL, 2012)
In the title compound, C21H19ClO3, the two cyclohexenone rings adopt half-chair conformations, whereas the pyran ring adopts a boat conformation. The 4-chlorophenyl ring is almost perpendicular to the plane through the four C atoms of the pyran ring [dihedral angle = 87.97 (6)degrees]. In the crystal, weak C-H center dot center dot center dot O hydrogen bonds link the molecules into a chain parallel to the a-axis.